Biodiversité et conservation néolibérale au Québec : la place de l’écotourisme - Jonathan Tardif; Bruno Sarrasin (Études Caribéennes)
Ecotourism is playing an increasingly important global role in reconciling biodiversity conservation with socio-economic development. Although ecotourism is often pointed to be instrumental to conservation, some scientific literature asserts that it rather allows capitalism to identify, open and colonize new spaces. In Québec, ecotourism appears on the political agenda of the State in the wake of the International Year of Ecotourism proclaimed in 2002. Several stakeholders have mobilized since then and present it as a strategy for sustainable development. Based on a critical approach, this paper presents the conditions for the emergence of ecotourism in Québec and the reasons that encourage social, political and economic stakeholders to choose to highlight biodiversity through and for ecotourism. This approach makes it possible to identify specificities, tensions and issues specific to Québec, but which echo what is observed elsewhere in the world.